2014
DOI: 10.1177/0049475514543941
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia in malaria: its usefulness in a clinical setting. A study from Western Rajasthan, India

Abstract: Any patient in a malaria endemic zone presenting with acute febrile illness and having thrombocytopaenia and anaemia should be alerted to the possibility of malarial infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The results of PbANKA infection in mice revealed that thrombocytopenia was observed as indicated by markedly decreased platelet counts. This finding was consistent with several studies that have shown malaria-associated thrombocytopenia [22][23][24]. Possible causes of thrombocytopenia during malaria include reduced platelet survival from peripheral destruction, enhanced sequestration, and decreased platelet production [25,26].…”
Section: Discussionsupporting
confidence: 92%
“…The results of PbANKA infection in mice revealed that thrombocytopenia was observed as indicated by markedly decreased platelet counts. This finding was consistent with several studies that have shown malaria-associated thrombocytopenia [22][23][24]. Possible causes of thrombocytopenia during malaria include reduced platelet survival from peripheral destruction, enhanced sequestration, and decreased platelet production [25,26].…”
Section: Discussionsupporting
confidence: 92%
“…This is the secondary analysis of the study and primary outcomes of the study have already been published [8]. Out of 100 patients, 58% were males and 42% were females, with male to female ratio of 1.4: 1.…”
Section: Resultsmentioning
confidence: 99%